Czas codzienny i czas odświętny – ich przenikanie w stylach życia współczesnej młodzieży - Peret-Drążewska, Paulina; Peret, Justyna (Kultura-Społeczeństwo-Edukacja, 2016)
Contemporary socio-cultural situation based on globalization make that many categories, concepts and theories required decontextualization, then recontextualization and redefinition. This process also applies to so intuitively obvious category, which is time. The specificity of the „survival” of time, perception and understanding have changed significantly influenced by current trends of modern times, such as the primacy of pleasure, the cult of success, mainstream consumerism, mass media influence. Because of these issues important and necessary it seems that re-thinking on modern understanding of time as a sociocultural category, which characterizes the quality and style of life of individuals as it exists in the current, post-modern space-time. This article provides theoretical considerations on the nature and specificity of everyday time and festive time in the context of current sociocultural based globalization processes. Assuming that the time and its fulfillment, or lifestyle are subject to the relationship of interdependence, the analysis will undergo a proposition about the consistency / heterogeneity of the individual’s life style presented in the context of the division of temporal existence of the unit on time everyday and festive time. Considerations will address today’s youth. It results from the specific lifestyle of this age group, which is due to the peculiarities of the development phase and the „soak” contemporary trends, in particular understands everyday / celebrating.